Subunit dimers of alpha-hemolysin expand the engineering toolbox for protein nanopores. - Hammerstein, A; Jayasinghe, L; Bayley, H (2011)
Staphylococcal α-hemolysin (αHL) forms a heptameric pore that features a 14-stranded transmembrane β-barrel. We attempted to force the αHL pore to adopt novel stoichiometries by oligomerizing subunit dimers generated by in vitro transcription and translation of a tandem gene. However, in vitro transcription and translation also produced truncated proteins, monomers, that were preferentially incorporated into oligomers. These oligomers were shown to be functional heptamers by single-channel recording and had a similar mobility to wild-type heptamers in SDS-polyacrylamide gels. Purified full-length subunit dimers were then prepared by using His-tagged protein. Again, single-channel recording showed that oligomers made from these dimers are functional heptamers, implying that one or more subunits are excluded from the central pore. Therefore, the αHL pore resists all structures except those that possess seven subunits immediately surrounding the central axis. Although we were not able to change the stoichiometry of the central pore of αHL by the concatenation of subunits, we extended our findings to prepare pores containing one subunit dimer and five monomers and purified them by SDS-PAGE. Two half-chelating ligands were then installed at adjacent sites, one on each subunit of the dimer. Single-channel recording showed that pores formed from this construct formed complexes with divalent metal ions in a similar fashion to pores containing two half-chelating ligands on the same subunit, confirming that the oligomers had assembled with seven subunits around the central lumen. The ability to incorporate subunit dimers into αHL pores increases the range of structures that can be obtained from engineered protein nanopores.